T-MOOC for Initial Teacher Training in Digital Competences: Technology and Educational Innovation - Martínez-Pérez, Sandra; Cabero-Almenara, Julio; Barroso-Osuna, Julio; Palacios-Rodríguez, Antonio (Frontiers in Education, 2022)
Massive open online courses (MOOCs) are perceived as emerging technologies for training and innovation in the educational context. They have become approaches for distance education in the face of the new challenges, changes, and crises experienced by the COVID-19 pandemic. They represent, in turn, new emerging opportunities as a response to the United Nations recommendations for open education and the development of sustainable goals. The presence of technologies in the development of educational tasks means that the acquisition of Digital Competences (DC) by teachers and students in training goes beyond the mere mastery of content and teaching methodologies. The research presented aims to analyze the educational possibilities of T-MOOCs for the development of DC in teachers, and as resources that favor autonomous and collaborative learning in innovative scenarios. The study sample is made up of 313 students of the Primary Education Degree at the University of Seville (Spain). For this purpose, two online questionnaires (Google Forms) were applied at the beginning of the course: the Digital Teaching Competence Questionnaire (DigCompEdu), and the Content Questionnaire: Digital Resources and Digital Pedagogy. The results obtained show that the students’ level of both digital competences and subject content is low to medium, so that training in educational technology is required for the acquisition of key digital competences. Based on the data obtained, the following actions are proposed: (a) The concretion of the contents structured by means of a learning guide and e-activities to be developed by the student body, taking into account the United Nations guidelines with regard to the Development of Sustainable Objectives; (b) The creation of a training and innovative environment under the T-MOOC architecture, based on open and distance learning due to the current health situation of COVID-19, which, on the one hand, empowers students to use digital tools, and on the other hand, facilitates the acquisition of the SDGs; and (c) The evaluation of the T-MOOC designed as a resource for autonomous, collaborative, guided learning in emerging contexts in which technologies and educational innovation play an important role for sustainable development.